Ion conducting methylcellulose-polyvinyl alcohol blend based electrolytes incorporated with ammonium thiocyanate for electric double layer capacitor application - Shamsuri, N.A. (John Wiley and Sons Inc, 2022)
Solid polymer electrolytes (SPEs) have received numerous attention for application in energy storage devices due to their safety performance and mechanical flexibility. However, further improvement of amorphousness and electrochemical performance is needed to realize the commercial potential of SPEs. In this work, a series of methylcellulose (MC) â polyvinyl alcohol (PVA) blend-based electrolyte doped with ammonium thiocyanate (NH4SCN) salt has been prepared using solvent casting technique. MC-PVA-NH4SCN electrolytes have been characterized and the most amorphous sample has been used as electrolyte in an electric double layer capacitor (EDLC). Thermogravimetric analysis is carried out to analyze the thermal stability of the electrolytes. From X-ray diffraction analysis, the addition of salt up to 40 wt decreases the percentage of crystallinity and crystallite size indicating the improvement in amorphousness of the polymer electrolytes. From transference number measurements analysis, it is revealed that ions are the dominant charge carriers. Linear sweep voltammetry shows that the most amorphous electrolyte is electrochemically stable in the potential range of â1.97 V to +1.90 V. Using the most amorphous MC-PVA-NH4SCN electrolyte, an EDLC has been fabricated and characterized using impedance technique, cyclic voltammetry and galvanostatic chargeâdischarge. Â© 2021 Wiley Periodicals LLC.